Increased Household Secondary Attacks Rates With Variant of Concern Severe Acute Respiratory Syndrome Coronavirus 2 Index Cases. (9th June 2021) - Buchan, Sarah A; Tibebu, Semra; Daneman, Nick; Whelan, Michael; Vanniyasingam, Thuva; Murti, Michelle; Brown, Kevin A
Abstract: We compared secondary attack rates in households with B.1.1.7 variant of concern (VOC) versus non-VOC index cases in a matched cohort in Ontario, Canada. The secondary attack rate for VOC index cases was 1.31 times higher than non-VOC index cases. This increase was particularly accentuated for asymptomatic or presymptomatic index cases.